Is siwak (chewing stick) an effective oral hygiene practice in modern society? - Tuti Ningseh Mohd Dom,; Haslinda Ramli,; Shahida Mohd Said,; Ahmad Munawar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islamic religion emphasised siwak (chewing stick) use as tooth and mouth cleaning tool, but the practice that modelled towards the Prophet’s Muhammad, peace be upon him (PBUH) behaviour is unclear. A study was conducted via individual semi-structured interviews, aimed to explore and map various aspects of the siwak practice from the perspective of contemporary Muslim scholars. These experts concurred that current siwak users vary in their observance towards the purpose, handling and timing of the siwak routine. It is a concern that deviations from the Prophet’s actual practices may limit the advantages of siwak, cause adverse effects on oral tissues and falsely portray siwak as an inferior option among modern communities. Findings from this study are derived from a triangulation of literatures and modern-day scholars’ interpretation which may be used as a basis for developing future guidelines on effective and safe siwak practice that is well-fitted to contemporary modern lifestyle.